Exploring the role of spin-triplets and trap states in photovoltaic processes of perovskite solar cells. Issue 18 (1st May 2018) - Lu, Kai; Zhao, Chen; Luan, Lin; Duan, Jiashun; Xie, Yulin; Shao, Ming; Hu, Bin
Abstract : Revealing the role of spin-triplets and trap states in the recombination and dissociation processes in PSCs. Abstract : The efficiency of perovskite solar cells is critically affected by the charge traps in the perovskite layer. Herein, we studied the recombination and dissociation processes of photo-excited states in perovskite solar cells with different densities and depths of the trap states in the perovskite layer using magneto-photocurrent measurements. The devices with lower density of traps show higher power conversion efficiency and negative magneto-photocurrent, whereas devices with higher density of deep traps exhibit lower power conversion efficiency and positive magneto-photocurrent. As the strong spin orbital coupling is induced by heavy atoms (Pb, I) in the perovskite materials, the original photo-excited spin-singlets ( φ m l =±1 φ ↑e↓h ) will transform into spin-triplets ( φ m l =0 φ ↑e↑h ) through intersystem crossing. In particular, the spin-triplets and trap states play an important role in photovoltaic actions of perovskite solar cells. Depending upon the depth of the traps, the spin-triplets can de-trap shallow charge carrier traps and subsequently contribute to the photocurrent in the perovskite solar cell, while the spin-triplets will be destroyed with the deep charge carrier traps, giving rise to non-radiative recombination in the perovskite solar cell. Our study elucidates the underlying mechanism, by which the spin configuration of photo-excited states, trap density and depth of traps impact the recombination and dissociation processes of the photo-excited states in perovskite solar cells based on the CH3 NH3 PbI3 (Cl) system.